2017
DOI: 10.1177/1024907917742877
|View full text |Cite
|
Sign up to set email alerts
|

Training in cardiopulmonary resuscitation provided by medical students, residents and specialists: A non-inferiority trial

Abstract: Introduction: No definitive answer has been given to the question 'who should teach cardiopulmonary resuscitation?' Healthcare professionals and high school teachers are mostly the trainers, but medical students are increasingly being used for this purpose. Methods: We divided 296 high school students in three groups based on trainer professional level. Medical students, anaesthesia and intensive care residents, and anaesthesia and intensive care specialists provided basic life support training. We tested thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…Where outcomes related to schoolchildren, eight studies measured confidence (Kirkpatrick Level 1b), knowledge (Kirkpatrick Level 2b) and skills (Kirkpatrick Level 2c) gained by the students post-training. 18 , 19 , 24 , 26 , 33 , 34 , 35 , 36 Two studies measured outcomes for medical students as CPR instructors, with the focus on professional practice skills (Kirkpatrick Level 2c) and CPR technical skills (Kirkpatrick Level 2c). 27 , 29 One study measured outcomes for both schoolchildren and medical students, namely confidence and theoretical knowledge in CPR (Kirkpatrick Levels 1b and 2b) for schoolchildren and confidence in professional practice outcomes (Kirkpatrick Level 1b) for medical students.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Where outcomes related to schoolchildren, eight studies measured confidence (Kirkpatrick Level 1b), knowledge (Kirkpatrick Level 2b) and skills (Kirkpatrick Level 2c) gained by the students post-training. 18 , 19 , 24 , 26 , 33 , 34 , 35 , 36 Two studies measured outcomes for medical students as CPR instructors, with the focus on professional practice skills (Kirkpatrick Level 2c) and CPR technical skills (Kirkpatrick Level 2c). 27 , 29 One study measured outcomes for both schoolchildren and medical students, namely confidence and theoretical knowledge in CPR (Kirkpatrick Levels 1b and 2b) for schoolchildren and confidence in professional practice outcomes (Kirkpatrick Level 1b) for medical students.…”
Section: Resultsmentioning
confidence: 99%
“… 14 , 15 , 16 , 17 However, the lack of hands-on practice for app-based training resources restricts the effectiveness of training, which means that other alternatives should be sought. Some studies have successfully utilised qualified health professionals such as physicians, nurses and paramedics in teaching schoolchildren, 18 , 19 , 20 , 21 but the cost and availability of such instructors renders these teaching models unsustainable.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Previous studies have shown that dispatcher-assisted cardiopulmonary resuscitation (DACPR) is essential in reducing the time to first compression and improving overall survival. (4)(5)(6) As DACPR requires clear communication between the dispatcher and the layperson who may not know how to perform cardiopulmonary resuscitation (CPR), the actual terms used in communicating the method of CPR are important. Poor communication could lead to delay in commencement of CPR, incorrectly performed CPR, or CPR not being performed altogether and, consequently, poor patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Many pharmaceutical companies and HTC searched for means for closer monitoring of these patients. Most of them are children and young adults who are shown to have a positive attitude toward learning trough technology ( 23 ), electronic devices turn out to be useful tools in monitoring and altogether the managing of hemophilia patients.…”
Section: Introductionmentioning
confidence: 99%